Modification of electrical properties of Al/p-Si Schottky barrier device based on 2?-7?-dichlorofluorescein - Soylu, Murat; Yahia, I. S.; Yakuphanoğlu, Fahrettin; Farooq, W. A. (Amer Inst Physics, 2011)
The charge conduction mechanism and electrical properties of Al/p-Si Schottky barrier device based on 2'-7'-dichlorofluorescein (DCF) were investigated by current density-voltage (J-V) and capacitance-voltage (C-V) methods. Thin film of DCF organic compound was deposited on p-Si substrate as an interfacial layer by spin-coating technique. The dark J-V characteristics indicate that the rectifying junction is formed at DCF/Al interface. The ideality factor and barrier height of the Al/DCF/p-Si Schottky diode are higher than that of Al/p-Si Schottky diode. The effect of the thickness of the DCF organic layer was investigated by evaluating electrical parameters, such as the barrier height, ideality factor, series resistance, and interface state density. It is seen that the thickness of the DCF layer significantly affects the electrical properties by influencing the space charge region of the Al/DCF/p-Si Schottky junction. The interface state density of the diode was determined using low-high frequency C-V plots and was of order of approximate to 10(11) eV(-1) cm(-2). The order of the interface state density of Al/DCF/p-Si is lower than most of metal/organic compound/inorganic semiconductor devices. The values of the barrier height of the studied diodes are significantly larger than those of conventional Al/p-Si Schottky diodes. The J-V curves in the reverse direction are taken and interpreted via both Schottky and Poole-Frenkel effects. Poole-Frenkel effect was found to be dominant in the reverse direction. (C) 2011 American Institute of Physics. [doi:10.1063/1.3647507]
Keywords: Nonpolymeric Organic-Compound; Interface State Density; Current-Voltage; Capacitance-Voltage; Temperature-Dependence; Diodes; Film; Height; Layer; Inhomogeneities